2020
DOI: 10.1002/cti2.1135
|View full text |Cite
|
Sign up to set email alerts
|

EGFR‐targeted CAR‐T cells are potent and specific in suppressing triple‐negative breast cancer both in vitro and in vivo

Abstract: Objectives. Triple-negative breast cancer (TNBC) is well known for its strong invasiveness, rapid recurrence and poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 93 publications
2
48
1
1
Order By: Relevance
“…This capability was exhibited in vitro and in vivo in a xenograft mouse model, with minimal off-tumor cytotoxicity. The activation of the interferon γ, granzyme-perforin-PARP and Fas-FADD-caspase signaling pathways in TNBC cells further confirm that CAR-T as an immunotherapy tool may be used to treat TNBC in the clinical setting 39 .…”
Section: Discussionmentioning
confidence: 61%
“…This capability was exhibited in vitro and in vivo in a xenograft mouse model, with minimal off-tumor cytotoxicity. The activation of the interferon γ, granzyme-perforin-PARP and Fas-FADD-caspase signaling pathways in TNBC cells further confirm that CAR-T as an immunotherapy tool may be used to treat TNBC in the clinical setting 39 .…”
Section: Discussionmentioning
confidence: 61%
“…We and others have reported that third-generation EGFR CAR-T cells exhibit potent and specific cytotoxicity against TNBC (6,7).…”
Section: Introductionmentioning
confidence: 84%
“…Cytotoxicity assays were performed using the xCELLigence Real-time Cell Analyzer (RTCA) System (ACEA Biosciences, San Diego) as described previously (6). MDA-MB-231 or EMT6 cells were seeded and cultured for 24 hours.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Although CAR T-cell therapy has limited use in solid tumors due to the shortage of unique tumor specific antigens, promising results have been reported in several recent in vivo studies [87,88]. Xia et al have successfully used EGFR CAR T with potent and specific antitumor activity against a triple-negative breast cancer model [89]. Likewise, CEA targeted CAR T-cells are also being tested for tumors expressing CEA [90].…”
Section: Genetically Modified T-lymphocytesmentioning
confidence: 99%